Rational Design of an Iron‐Based Catalyst for Suzuki–Miyaura Cross‐Couplings Involving Heteroaromatic Boronic Esters and Tertiary Alkyl Electrophiles. Issue 13 (25th February 2020) - Crockett, Michael P.; Wong, Alexander S.; Li, Bo; Byers, Jeffery A.
Abstract: Suzuki–Miyaura cross‐coupling reactions between a variety of alkyl halides and unactivated aryl boronic esters using a rationally designed iron‐based catalyst supported by β‐diketiminate ligands are described. High catalyst activity resulted in a broad substrate scope that included tertiary alkyl halides and heteroaromatic boronic esters. Mechanistic experiments revealed that the iron‐based catalyst benefited from the propensity for β‐diketiminate ligands to support low‐coordinate and highly reducing iron amide intermediates, which are very efficient for effecting the transmetalation step required for the Suzuki–Miyaura cross‐coupling reaction. Abstract : Nacnac! Who's there? A mechanistically driven approach to Suzuki–Miyaura cross‐coupling with a nacnac iron‐based catalyst enables the facile construction of C(sp 3 )−C(sp 2 ) bonds with heteroaromatic boronic esters. Additional advancements allow for the construction of all carbon quaternary centers with no observable isomerization.